2015
DOI: 10.18869/acadpub.hms.21.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Prescribing One Dose or Two Doses of Injecting Betamethasone for Pregnant Women on Preterm Infants Outcomes

Abstract: Aims: The use of corticosteroids and abandoning the delivery are of preventive actions of newborns' respiratory distress syndrome. The aim of this clinical trial was to compare the effect of one versus two doses of Betamethasone on the outcomes of preterm infants. Materials & Methods: In this quasi-experimental clinical trial, 100 preterm labor pregnant women who referred to Sanandaj Be'sat Hospital in 2013 were selected by purposive sampling method and were divided into one dose (12mg Betamethasone) and two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a double-blind clinical trial conducted by Mansouri et al, the administration of betamethasone reduced the 24-hour NICU stay (47). On the other hand, Saymari et al reported no significant effect of betamethasone concerning a decrease in NICU admission (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a double-blind clinical trial conducted by Mansouri et al, the administration of betamethasone reduced the 24-hour NICU stay (47). On the other hand, Saymari et al reported no significant effect of betamethasone concerning a decrease in NICU admission (15).…”
Section: Discussionmentioning
confidence: 96%
“…Previous research showed that betamethasone has extremely fewer side effects compared to dexamethasone (14). Further, evidence suggests that prenatal benefits, as well as maternal and neonatal complications are not associated with multiple courses of corticosteroids compared to a single course (15). The National Institutes of Health Consensus Development Panel concluded that the full benefits of taking corticosteroids appear in infants 24 hours after the treatment.…”
mentioning
confidence: 99%